2017
DOI: 10.1038/hr.2017.32
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific blood pressure correction technique for arterial stiffness: evaluation in a cohort on anti-angiogenic medication

Abstract: Arterial pulse wave velocity (PWV) depends on blood pressure (BP). Correction of PWV for BP is commonly performed using a statistical approach, requiring a patient cohort. We recently developed a mechanistic, model-predictive approach to assess BP-independent changes in carotid PWV (cPWV) at the level of the individual. The goal of the present study is to compare our novel technique to conventional statistical correction, in the context of anti-cancer therapy using anti-angiogenic drugs (AADs). AADs frequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Transit time PWV and single-point measures (DC, CC, and single-point PWV) are all well known to show pressure dependence, requiring adjustment for blood pressure (123,126). Statistical adjustments are a valid and powerful approach when groups or populations are considered but lack applicability in the setting of individual patient management (121,124). Two of the selected studies (2 of 63 studies) used the cardio-ankle vascular index (CAVI) obtained by measuring transit time over the heart-to-ankle trajectory (116,136) to account for pressure dependence by approximating the pressure-area relationship by a single exponential (akin to stiffness index ␤; see Ref.…”
Section: Content Analysis Of Selected Papersmentioning
confidence: 99%
“…Transit time PWV and single-point measures (DC, CC, and single-point PWV) are all well known to show pressure dependence, requiring adjustment for blood pressure (123,126). Statistical adjustments are a valid and powerful approach when groups or populations are considered but lack applicability in the setting of individual patient management (121,124). Two of the selected studies (2 of 63 studies) used the cardio-ankle vascular index (CAVI) obtained by measuring transit time over the heart-to-ankle trajectory (116,136) to account for pressure dependence by approximating the pressure-area relationship by a single exponential (akin to stiffness index ␤; see Ref.…”
Section: Content Analysis Of Selected Papersmentioning
confidence: 99%
“…8) Furthermore, analyses of carotid PWV in patients with cancer treated with sunitinib or sorafenib revealed the BP-independent effects of these drugs on arterial stiffness. 25) This study adjusted the angiogenesis inhibitor-induced changes of BP and showed a BP-independent increase in carotid PWV, 25) thus suggesting the possibility that the long-term inhibition of angiogenesis due to sorafenib and axitinib could detrimentally and BP independently increase aortic stiffness and develop arteriosclerosis in our patient.…”
Section: Discussionmentioning
confidence: 67%
“…PWV, as well as DC, are well known to be pressure dependent and require blood pressure adjustment [199]. Adjustment is valid when considering group analyses, but lacks applicability in the use of individual cases [32,200].…”
Section: Assessing Vascular Remodeling and Diseasementioning
confidence: 99%